Artrópodos associados à copa de Attalea phalerata Mart. (Arecaceae), na região do Pantanal de Poconé, Mato Grosso, Brasil - Santos,Geane Brizzola dos (2003)
Six individuals of the palm A. phalerata, in Poconé floodplains of Mato Grosso, were sprayed with a synthetic pyrethroid (0.25% concentration) in order to study the biomass, diversity, and richness of the canopy arthropods. A total of 17,188 (238.7±80.6 ind./m²) arthropods belonging to 22 Orders, was collected in a 72 m² funnel area. Two hours after spraying, 58.9% of the total number fell into the funnels, 37.6% was obtained by shaking the trees, and finally, 3.5% after cutting and washing all the palm leaves. The Coleoptera (27.4%), Hymenoptera-Formicidae (19.0%), Collembola (13.6%), Psocoptera (10.7%), Diptera (9.0%) and Araneae (6.4%) were the predominant. The total biomass was 15.1 g dry weight (0.4mg/m²; 0.13+0.04/tree). A total of 4,715 beetles representing 48 families and 326 morphospecies were obtained. Tenebrionidae (22.9%), Curculionidae (22.0%), Carabidae (10.9%) and Staphylinidae (7.9%) were the most abundant, while Curculionidae (44 spp.), Staphylinidae (40 spp.) and Chrysomelidae (34 spp.) presented the largest number of morphospecies. Herbivores (37.5%) were the dominant in the trophic guilds of adult Coleoptera, followed by predators (35.4%), fungivores (14.6%), and saprophages (12.5%). Although most arthropod Orders were represented in all the palms sampled, analysis of variance showed no significant differences in their composition, however there was a significant difference in their frequency of occurrence.